External irradiation with or without long-term androgen suppression for prostate cancer with high metastatic risk: 10-year results of an EORTC randomised study - Bolla, Michel; Van Tienhoven, Geertjan; Warde, Padraig; Dubois, Jean Bernard; Mirimanoff, René-Olivier; Storme, Guy; Bernier, Jacques; Kuten, Abraham; Sternberg, Cora; Billiet, Ignace; Torecilla, José Lopez; Pfeffer, Raphael; et al. (The lancet oncology, 2010)
We did a randomised phase 3 trial assessing the benefit of addition of long-term androgen suppression with a luteinising-hormone-releasing hormone (LHRH) agonist to external irradiation in patients with prostate cancer with high metastatic risk. In this report, we present the 10-year results. For this open-label randomised trial, eligible patients were younger than 80 years and had newly diagnosed histologically proven T1–2 prostatic adenocarcinoma with WHO histological grade 3 or T3–4 prostatic adenocarcinoma of any histological grade, and a WHO performance status of 0–2. Patients were randomly assigned (1:1) to receive radiotherapy alone or radiotherapy plus immediate androgen suppression. Treatment allocation was open label and used a minimisation algorithm with institution, clinical stage of the disease, results of pelvic-lymph-node dissection, and irradiation fields extension as minimisation factors. Patients were irradiated externally, once a day, 5 days a week, for 7 weeks to a total dose of 50 Gy to the whole pelvis, with an additional 20 Gy to the prostate and seminal vesicles. The LHRH agonist, goserelin acetate (3·6 mg subcutaneously every 4 weeks), was started on the first day of irradiation and continued for 3 years; cyproterone acetate (50 mg orally three times a day) was given for 1 month starting a week before the first goserelin injection. The primary endpoint was clinical disease-free survival. Analysis was by intention to treat. The trial is registered at ClinicalTrials.gov, number NCT00849082. Between May 22, 1987, and Oct 31, 1995, 415 patients were randomly assigned to treatment groups and were included in the analysis (208 radiotherapy alone, 207 combined treatment). Median follow-up was 9·1 years (IQR 5·1–12·6). 10-year clinical disease-free survival was 22·7% (95% CI 16·3–29·7) in the radiotherapy-alone group and 47·7% (39·0–56·0) in the combined treatment group (hazard ratio [HR] 0·42, 95% CI 0·33–0·55, p<0·0001). 10-year overall survival was 39·8% (95% CI 31·9–47·5) in patients receiving radiotherapy alone and 58·1% (49·2–66·0) in those allocated combined treatment (HR 0·60, 95% CI 0·45–0·80, p=0·0004), and 10-year prostate-cancer mortality was 30·4% (95% CI 23·2–37·5) and 10·3% (5·1–15·4), respectively (HR 0·38, 95% CI 0·24–0·60, p<0·0001). No significant difference in cardiovascular mortality was noted between treatment groups both in patients who had cardiovascular problems at study entry (eight of 53 patients in the combined treatment group had a cardiovascular-related cause of death vs 11 of 63 in the radiotherapy group; p=0·60) and in those who did not (14 of 154 vs six of 145; p=0·25). Two fractures were reported in patients allocated combined treatment. In patients with prostate cancer with high metastatic risk, immediate androgen suppression with an LHRH agonist given during and for 3 years after external irradiation improves 10-year disease-free and overall survival without increasing late cardiovascular toxicity. AstraZeneca; Ligue Nationale Contre le Cancer (France), through the EORTC Charitable Trust.